Trends of upper urinary tract stone management in a high volume stone center in Saudi Arabia, 12 years analysis - Rakan Al Darrab (Urology Annals, 2020)
Introduction: Urolithiasis is a common urological problem globally with tremendous health and economic burden. In Saudi Arabia, an estimation has shown that the risk of developing a stone episode is 50% higher than that in Western countries. About 20% of males would experience at least one episode by 70 years of age. The introduction of minimally invasive and noninvasive methods such as shockwave lithotripsy (SWL), ureteroscopy (URS), and percutaneous nephrolithotripsy (PCNL) has driven the urologists to more complex decision-making with a noted variance in management options. Objectives and Methods: The objective of the study was to observe the trend of upper urinary tract stone management in our institution in the past 12 years. Methods: Charts of patients who underwent upper urinary tract lithotripsy procedures of any kind were reviewed. The information obtained included, patient's age, surgeon, surgery type, stone size, stone location, and duration of surgery. Analysis: The data obtained were from 2006 to 2016. Excel sheets used for the collection of data and SPSS software was used for analysis. Results: The results showed that the majority of the patients were males accounting for 65%. ESWL was the predominant approach from 2006 to 2010. In 2006, ESWL accounted for 77.7% of the cases, 76% in 2007, 70% in 2008, 64% in 2009, and 62% in 2010. However, in 2011, the rates dropped to almost 18% and URS rates have increased from a few cases per year to 64%. The frequency of URS continued to rise through the years until 2015 where URS rates reached 75%. During the 12-year period, URS is the most common upper tract procedure conducted when compared to ESWL and PCNL, accounting for 63%, 16%, and 20%, respectively. Conclusion: In our institution, the frequency of URS rose over the years being the most abundant procedure done. ESWL rates have decreased over the years.